SARS-CoV-2 and gastrointestinal diseases - Sha, Ailong; Liu, Yi; Zhao, Xuewen (Frontiers in Microbiology, 2023)
Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the causative agent of the novel coronavirus disease (COVID-19) pandemic, which has caused serious challenges for public health systems worldwide. Literature review: SARS-CoV-2 invades not only the respiratory system, but also the digestive system, causing a variety of gastrointestinal diseases. Significance: Understanding the gastrointestinal diseases caused by SARS-CoV-2, and the damage mechanisms of SARS-CoV-2 to the gastrointestinal tracts and gastrointestinal glands are crucial to treating the gastrointestinal diseases caused by SARS-CoV-2. Conclusion: This review summarizes the gastrointestinal diseases caused by SARS-CoV-2, including gastrointestinal inflammatory disorders, gastrointestinal ulcer diseases, gastrointestinal bleeding, and gastrointestinal thrombotic diseases, etc. Furthermore, the mechanisms of gastrointestinal injury induced by SARS-COV-2 were analyzed and summarized, and the suggestions for drug prevention and treatment were put forward for the reference of clinical workers.